What is the story of Wonder Woman? - Korté, Steven (Penguin Workshop, 2019)
Describes the history of the comic book superhero Wonder Woman, discussing her creator, the rising popularity of comics, the changes in her character over time, and her legacy today. Includes black-and-white illustrations and sidebars.